Proceedings of the 11th Conference on Advances in Computer Entertainment Technology 2014
DOI: 10.1145/2663806.2663874
|View full text |Cite
|
Sign up to set email alerts
|

Towards an olfactory computer-dream interface

Abstract: Memory and emotion are an ever-important aspect of Human Computer Interaction. While we are researching new interfaces for emotional and experience communication through multisensory communication, there is one aspect of our emotional perception that has been largely ignored in the process: dreaming. We propose to take a new direction by studying the perception of emotions during sleep and how they can be affected through external stimuli via novel user interfaces. In this position poster we take results from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Active research has found that using olfactory stimulus can enhance fear extinction during slowwave sleep condition when same olfactory context re-exposes to humans who have faced contextual fear condition during awake periods (Hauner et al 2013;Braun and Cheok 2014).…”
Section: Duis For Basic Human Senses: Smellmentioning
confidence: 99%
“…Active research has found that using olfactory stimulus can enhance fear extinction during slowwave sleep condition when same olfactory context re-exposes to humans who have faced contextual fear condition during awake periods (Hauner et al 2013;Braun and Cheok 2014).…”
Section: Duis For Basic Human Senses: Smellmentioning
confidence: 99%
“…imagineeringinstitute.org), we are also working on digitizing taste experiences. Recent research has forwarded both taste and smell digital technologies such as Digital Sour Taste Interface [66], Thermal Sweet Taste Interface [67], and Scentee [68]. The hope is that the literature on crossmodal correspondences may help to enhance digital taste and smell communication (see [69], for a review).…”
Section: Future Researchmentioning
confidence: 99%